Bāṃlādeśera iuniẏana parishada sacibagaṇera sāmājika paṭabhūmi - Rahman, Mohammad Shafiqur (Nyāśanāla Inasṭiṭiuṭa aba Lokāla Gabharṇameṇṭa, 1993)
Appraisal on social background of secretaries of union parishads in Bangladesh.